2023
DOI: 10.26682/ajuod.2023.26.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental Feeding on The Weight of Silk Glands And Larval Development of Mulberry Silkworm (bombyx Mori)

Abstract: The study aimed to revive the Sericulture in our area after three decades of absence and to investigate the role of supplemental feeding on silk glands, larval growth, and some economic traits of cocoons of mulberry silkworms (Bombyx mori). Larvae of 5th instar fed on vitamin C during their 4 th and 5 th instars showed a significant increase in their length (6.953 ± 0.248 mm). Mature larvae fed on vitamin C showed a significant increase in their weight (3.690±0.129 g). Vitamin C was the most effective suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Furthermore, Muzamil et al (2023) confirmed the addition high concentrations of amino acids in feeding of mulberry silkworm leads to the toxicity so, it is important to use specific concentration of amino acids for normal growth. Helan and Zahra (2023) reported mulberry leaves smeared with 4% honey increasing 5 th larval weight. The overall growth rate increased (8.3%) at honey (2%) Sharma et al, (2023).…”
Section: Biological Charactersmentioning
confidence: 99%
“…Furthermore, Muzamil et al (2023) confirmed the addition high concentrations of amino acids in feeding of mulberry silkworm leads to the toxicity so, it is important to use specific concentration of amino acids for normal growth. Helan and Zahra (2023) reported mulberry leaves smeared with 4% honey increasing 5 th larval weight. The overall growth rate increased (8.3%) at honey (2%) Sharma et al, (2023).…”
Section: Biological Charactersmentioning
confidence: 99%